THE INFLUENCE OF ELECTORAL SYSTEMS ON THE FORMATION OF THE PARTY SYSTEM AND THE MECHANISM OF POLITICAL POWER IN UKRAINE - Телуха, Є.В. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2015)
The paper studied the influence of electoral systems on the formation of the modern party system and the mechanism of political power in Ukraine. Accentuated that the choice of the type of party system formation requires the practical assessment of policy needs and opportunities of the state, which in turn is crucial for the functioning of the political system of society as a whole.